Dynamic and stochasitc rational behavior - Nail Kashaev; Charles Gauthier; Victor H. Aguiar (The University of Western Ontario, Department of Economics, 2023)
We analyze consumer demand behavior using Dynamic Random Utility Model (DRUM). Under DRUM, a consumer draws a utility function from a stochastic utility process in each period and maximizes this utility subject to her budget constraint. DRUM allows unrestricted time correlation and cross-section heterogeneity in preferences. We fully characterize DRUM for a panel data of consumer choices and budgets. DRUM is linked to a finite mixture of deterministic behavior represented as the Kronecker product of static rationalizable behavior. We provide a generalization of the Weyl-Minkowski theorem that uses this link and enables conversion of the characterizations of the static Random Utility Model (RUM) of McFadden-Richter (1990) to its dynamic form. DRUM is more flexible than Afriat's (1967) framework for time series and more informative than RUM. We show the feasibility of the statistical test of DRUM in a Monte Carlo study.
Keywords: C10; C33; D11; D12; D15; 330; dynamic random utility; revealed preference